LAUGH, NOT WAR: HUMOR, SATIRE AND THE DISSOLUTION OF YUGOSLAVIA - Ilina Jakimovska (EtnoAntropoZum, 2020)
The article presents a concise review of political criticism through the medium of humor and satire, at the time of ex-Yugoslavia and during its dissolution. It covers several important magazines and individual authors from ex-Yugoslav republics that, in difficult times for the freedom of speech, have shown dignity and courage to describe, criticize and warn regarding existing nationalisms and the futility of wars.